Distribution Notes on Western and Southwestern Snails; Comments on Arion Fasciatus (Nilsson) From Minnesota: Glebula in Oklahoma - Branley A. Branson (Hello World!, 1969)
During the last several years I have accumulated a few gastropod records in my files which are probably of interest to students of the western fauna.